1997
DOI: 10.1007/s001250050685
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D, glucose tolerance and insulinaemia in elderly men

Abstract: We have been interested in environmental factors which may contribute to the development of non-insulin-dependent diabetes mellitus (NIDDM). Previous analysis of dietary factors in a cohort of elderly Dutch people has shown that regular fish eating reduced the 4-year risk of glucose intolerance in normoglycaemic individuals [1]. Experimentally vitamin D is required for normal insulin secretion and glucose tolerance [2]. Since fish can be an important dietary source of vitamin D this sub-study was designed to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
163
0
8

Year Published

1998
1998
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 282 publications
(186 citation statements)
references
References 7 publications
15
163
0
8
Order By: Relevance
“…In vivo, however, clear glucose intolerance was observed already at 100 days of age in female and even more pronounced in male vitamin D-deficient NOD mice. There are several reports on the link between vitamin D deficiency and the pathogenesis of insulin resistance, impaired glucose intolerance and even Type 2 diabetes in humans [45,46]. Therefore the impaired glucose intolerance found in the vitamin Ddeficient NOD mice at 100 days of age might be explained in part by an increased insulin resistance in these animals, since insulin secretion and synthesis were comparable to those found in vitamin D-sufficient NOD mice.…”
Section: Discussionmentioning
confidence: 86%
“…In vivo, however, clear glucose intolerance was observed already at 100 days of age in female and even more pronounced in male vitamin D-deficient NOD mice. There are several reports on the link between vitamin D deficiency and the pathogenesis of insulin resistance, impaired glucose intolerance and even Type 2 diabetes in humans [45,46]. Therefore the impaired glucose intolerance found in the vitamin Ddeficient NOD mice at 100 days of age might be explained in part by an increased insulin resistance in these animals, since insulin secretion and synthesis were comparable to those found in vitamin D-sufficient NOD mice.…”
Section: Discussionmentioning
confidence: 86%
“…This finding further suggests that hypovitaminosis D is associated with severe glucose intolerance and insulin-dependency in diabetic subjects. Experimentally, vitamin D is required for normal insulin secretion and glucose tolerance [30], and hypovitaminosis D may be a significant risk factor for glucose intolerance in diabetic patients [8]. It has recently been reported that positive correlation of serum 25-OHD concentration with insulin sensitivity and a negative effect of hypovitaminosis D on β cell function were found in normal population, and that subjects with hypovitaminosis D had a greater prevalence of components of metabolic syndrome than did subjects without hypovitaminsosis D [31].…”
Section: Discussionmentioning
confidence: 99%
“…In type 1 diabetes, it is apparent that osteopenia occurs especially in the young-onset type 1 diabetes, and that the demineralization process seems to be related to fasting blood glucose concentrations and HbA1c [5][6][7]. Moreover, it has also been suggested that hypovitaminosis D may be a significant risk factor for glucose intolerance [8]. High prevalence of hypovitaminosis D in type 2 diabetes patients has been reported [9,10], whereas Ishida et al [11] could not find any difference in such patients from the control, suggesting that more precise analysis of the relationship between the 25-OHD level and the clinical manifestations of type 2 diabetes is needed.…”
mentioning
confidence: 99%
“…Findings of several studies suggest that higher intake of polyunsaturated fat and possibly long-chain n-3 fatty acids could be beneficial in prevention of type II diabetes, whereas higher intake of saturated fat and trans-fat may be detrimental (Hu et al, 2001b). Other dietary factors that have been related to reduced risk of type II diabetes include coffee (van Dam & Feskens, 2002;Tuomilehto et al, 2004), dairy products , and vitamin D (Baynes et al, 1997).…”
Section: Introductionmentioning
confidence: 99%